Expanding durable solutions for refugees: possibilities for developing education pathways in Australia. Issue 2 (2nd September 2022) - Evans, Rosie; Baker, Sally; Wood, Tamara
ABSTRACT: As the number of people forced to flee their homes continues to grow each year, traditional legal frameworks for protecting those who move, such as refugee and human rights law, are increasingly under strain. The limited scope of these frameworks, and diminishing political will to implement them, leave countless refugees and other forced migrants with little chance of finding long-term safety and rebuilding their lives. It is increasingly apparent that traditional refugee resettlement programs offered by countries such as Australia are not enough. In this article, we offer a comparative document analysis of the options for developing dedicated higher education migration pathways (education pathways) for refugees as a 'complement' to refugee resettlement in Australia. First, we discuss the limited availability of resettlement spaces and higher education opportunities for refugees. Second, we explore complementary 'education pathways' as a potential solution to these problems. Third, we critically examine several such pathways already underway in Canada, Mexico and Japan. Lastly, we consider potential models that could be utilised in Australia, and how they would, or could, interact with Australia's existing humanitarian programs.